2014
DOI: 10.18352/rg.9398
|View full text |Cite
|
Sign up to set email alerts
|

Women on the Fault Lines of Faith: Pussy Riot and the Insider/Outsider Challenge to Post-Soviet Orthodoxy

Abstract: This article examines the explosive reaction to 'Punk Prayer' as a religious act. It argues that the power of the performance as iconoclash resulted from the fact that it tapped, resonated with and disturbed Russia's Orthodox culture through its appropriation of Orthodox sound, space and symbols -namely, the image of Mary, the Mother of God. The perceived position of its performers as insiders or outsiders to Orthodoxy, the evaluation of the sincerity of Punk Prayer as prayer and the paradoxical role that gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…15 The "Pussy Riot Incident" is a particularly complex issue as it was, on the one hand, an act of protest against government and ecclesiastical corruption, and, on the other hand, an act of trespass in private sacred space that was deemed highly offensive by much of the Russian populace. For nuanced and competing assessments of what was at stake in Pussy Riot's act of protest see both "An Appeal to Mary: An Analysis of Pussy Riot's Punk Performance in Moscow" (Denysenko 2013), and "Women on the Fault Lines of Faith: Pussy Riot and the Insider/Outsider Challenge to Post-Soviet Orthodoxy" (Shevzov 2014). …”
Section: The Edict Of Milan: Edict Of Toleration or Edict Increasing mentioning
confidence: 99%
“…15 The "Pussy Riot Incident" is a particularly complex issue as it was, on the one hand, an act of protest against government and ecclesiastical corruption, and, on the other hand, an act of trespass in private sacred space that was deemed highly offensive by much of the Russian populace. For nuanced and competing assessments of what was at stake in Pussy Riot's act of protest see both "An Appeal to Mary: An Analysis of Pussy Riot's Punk Performance in Moscow" (Denysenko 2013), and "Women on the Fault Lines of Faith: Pussy Riot and the Insider/Outsider Challenge to Post-Soviet Orthodoxy" (Shevzov 2014). …”
Section: The Edict Of Milan: Edict Of Toleration or Edict Increasing mentioning
confidence: 99%
“…A growing body of feminist, social science, and area studies scholarship has shown how Pussy Riot's punk prayer and its aftermath illuminated key tensions that animated Russian politics and activism in 2012, in particular the repressive power of the Putin-era state, the influence of conservative Russian Orthodoxy and its relationship with state nationalism, and the central roles of gender and spectacles of gendered violence in the Putin government's consolidation of authoritarian power (Bernstein, 2013;Johnson, 2014;Rourke and Wiget, 2016;Schroeder and Karpov, 2013;Shevzov, 2014;Sperling, 2015;Tolstaya, 2014). Scholars have also examined what the Pussy Riot case reveals about new forms of feminist protest in Russia (Johnson, 2014) and globally (Baer, 2016) and how local feminist organising is transformed through transnational solidarity efforts and the circulation of prominent cases like that of Pussy Riot (Channell, 2014;Groeneveld, 2014;Wiedlack and Neufeld, 2014).…”
Section: Introductionmentioning
confidence: 99%